2012
DOI: 10.1007/s13277-012-0548-3
|View full text |Cite
|
Sign up to set email alerts
|

Activation of β-catenin signaling is critical for doxorubicin-induced epithelial–mesenchymal transition in BGC-823 gastric cancer cell line

Abstract: The epithelial-mesenchymal transition (EMT) is a fundamental process governing morphogenesis in multicellular organisms and has recently been implicated in promoting carcinoma invasion and metastasis. Besides their therapeutic effects, accumulating evidences suggest that chemotherapeutic agents also induced EMT and enhanced the malignancy of treated cancer cells; however, the mechanism(s) still remains unclear. Here, we investigated the role of β-catenin signaling in doxorubicin (Dox)-induced EMT in human gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 26 publications
3
22
0
Order By: Relevance
“…These data indicated that the EMT phenotype was inherited in ltDSCs. We previous reported that β-catenin signaling was activated after 48 h Dox treatment (Han et al, 2013). Here we also found that the mRNA level of β-catenin was higher in ltDSCs than parental cells (Figure 2a), suggesting the sustained activation of β-catenin signaling in ltDSCs.…”
Section: Emt Status Were Maintained In Ltdscssupporting
confidence: 81%
See 3 more Smart Citations
“…These data indicated that the EMT phenotype was inherited in ltDSCs. We previous reported that β-catenin signaling was activated after 48 h Dox treatment (Han et al, 2013). Here we also found that the mRNA level of β-catenin was higher in ltDSCs than parental cells (Figure 2a), suggesting the sustained activation of β-catenin signaling in ltDSCs.…”
Section: Emt Status Were Maintained In Ltdscssupporting
confidence: 81%
“…These long term cultured DSC still exhibited a typical mesenchymal morphology and expressed high levels of mesenchymal cell markers and chromatin reprogramming factors. Our previous study showed that 48 h Dox treatment could induced EMT in BGC-823 cells (Han et al, 2013), which precluded the possibility that the EMT phenotype of ltDSCs was caused by DNA mutation in such short time of drug exposure. Together, our data suggested that an epigenetic mechanism was involved in the maintenance of EMT in ltDSCs.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Qu et al (100) reported that overexpressed sFRP1 is correlated with EMT induction in GC cells as well as lymph node migration and reduced survival time. Han et al (101) established an EMT model by treating BGC-823 cells with doxorubicin and elaborated upregulation of β-catenin, LEF1, c-Myc which indicates activated β-catenin signaling. Thereafter, noticeable reversion of EMT biomarkers was found when applying indomethacin or siRNA to stamp down β-catenin.…”
Section: Interaction Between Emt and Wnt/β-catenin Signaling In Gastrmentioning
confidence: 99%